Study of current ripple characteristics of inverter-fed multiple three-phase AC motors - Anwar Muqorobin; Pekik Argo Dahono (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The need of higher power and more reliable applications have promoted the use of multiphase alternating current (AC) drives. Mostly the motors are used in wide speed operation range. To control the motors, in the low speed region the motors are operated under pulse width modulation (PWM) mode and in the high speed region, they use square wave mode. In this paper, the current ripple characteristics of inverter-fed multiple three-phase AC motors that are operated under dual mode operation (PWM and square wave modes) are investigated. The optimal motor stator winding configuration will be optimized from the viewpoint of inverter input and motor current ripples. Six-phase motor is used as the representative of even-phase motors and nine-phase motor for odd-phase motors. It is found that nine-phase motor is better than six-phase motor if dual mode operation is desired. Experimental results are incorporated to support the analytical results.